PERBEDAAN WAKTU PEMBERIAN TERAPI MUSIK KLASIK (MOZART) TEHADAP TINGKAT NYERI HAID (DISMENORHE) PADA REMAJA PUTRI - Paramitha, Firsty Ayu (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Dismenorhe is a pain that is felt in the stomach, derived from cramp the uterus and occursduring menstruation.One therapy non pharmacological is intervention therapy classical music(mozart).The purpose of this research is to see perbedaanwaktu the provision of therapy classicalmusic (mozart) on the level of painful menstruation dismenorhe in reamaja daughter. Design thisresearch is his experiments with rancangn static group compariman.To technique the sample doneby is purposive sampling, with total sample is as many as 30 people.Population adolescent girlsthat experienced dismenorhe in sman 1 vii the koto sei.sarik. Pain dismenorhe data collected byusing lemblembar ceklis mankoski. Of the test statistics use anova obtained rata-rata value in thecontrol the rate of the painful menstruation 7.75 .Rata-rata the painful menstruation after donetherapy classical music (mozart) for 10 minutes is 6.55 , for 20 minutes is 6.05 , . for 30 minutesis 4.95 worth pvalue 0.000. Based on the results of above can be concluded that the therapyclassical music (mozart) 30 minutes more effective against the decline in pain menstruation inadolescent girls.Advice research is expected adolescent girls start to do therapy classical music(mozart) to reduce pain dismenorhe without medication pharmacological.Keywords: Classical Music (Mozart), Menstrual Pain (Dismenorhe)